(3GdJShjb hGdeSDhdjI GdGLJeGYjI (B/s - (3GdHcQj, KGeQ jGSQs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2001)
(3GdHYO GdJGQjNj deSDhdjI GdGLJeGYjI h JYQjagG h eaghegG h JfGhd GdeSDhdjI GdGLJeGYjI Hjf GdJCjjO h GdeYGQVI h GdJWQb Gdi JCKjQGJ GdHjFI Ydi efXeGJ GdGYeGd aj JWHjb GdeSDhdjI GdGLJeGYjI h cPG ESJQGJjLjI GdYdGbI Hjf GdJCKjQGJ GdbGfhfjI h GdeSDhdjI GdGLJeGYjI h GdJNWjW ddeSDhdjI GdGLJeGYjI HGYJeGO GdTcGhi h GdeTcdGJ GdeQJHWI HGdeLJeY h cPG Gdeaghe GdGLJeGYj ddJShjb h GdeSDhdjI GdGLJeGYjI h MeGjI GdeSJgdc h Mbhbg h GNdGbjGJ GdJShjb h GNjQG GdOQGSGJ GdSGHbI aj GdeSDhdjI GdGLJeGYjI(B.s
(3GdeQGLY U(B.159s
Keywords: (3GdJShjbs; (3GdeSDhdjI GdGLJeGYjIs